Pitirim Sorokin – Dynamics of social and cultural changes - Mirčov, Velizar (Sociološki pregled, 2021)
The paper gives a review and a critical overview of the theoretical approach to the dynamics of cultural and social changes of renowned sociologist Pitirim Sorokin. The first part of the paper is dedicated to the description of the most relevant theoretical contributions contained in Sorokin’s most important book Social and Cultural Dynamics. In the second part of the paper, there is a critical overview by the author of this text of Sorokin’s sociocultural dynamics theory, as well as of other authors who have studied Sorokin’s approach. The conclusion of this paper is that Sorokin’s approach is a very significant theoretical contribution to sociology, but also that his theory does not dedicate sufficient attention to external factors as the causes of sociocultural dynamics.